Orbital US-based characteristics in Graves’ disease-associated autoimmune ophthalmopathy (Ukrainian Journal of Ophthalmology, 2025)
Background: Autoimmune ophthalmopathy (AO) may develop in as much as 90% patients with Graves’ disease (GD), and may lead to visual disability. Adequate imaging of orbital structures allows planning adequate treatment in most cases, contributing to better treatment outcomes in patients with AO.Purpose: To examine orbital ultrasound (US)-based characteristics in patients with GD-associated AO.Material and Methods: One hundred patients with GD-associated AO underwent a comprehensive examination that included (1) determination of AO activity by clinical activity score (CAS), (2) measurements of thyrotropin (TSH), free thyroxine (FT4), free triiodothyronine (FT3), and TSH-R-Ab levels; and (3) US of the thyroid gland and orbital tissue. In addition, 31 of these patients underwent magnetic resonance imaging (MRI). The Student t test was used for statistical analyses. The level of significance p ? 0.05 was assumed. Data are presented as mean ± SEM.Results: One hundred patients (73 women and 27 men; age, 18 to 79 years; mean age, 48.42 ± 13.56 years; mean disease duration, 3.1 ± 2.2 years) with GD-associated AO were included in this study. Of these, 65% were euthyroids, whereas 18% and 17% were found to have clinical hyperthyroidism and subclinical hyperthyroidism, respectively. As expected, the mean TSH-R-Ab level (11.07±1.03 U/mL) was higher than normal ( 3 (active disease), and 51 had a CAS score < 3 (non-active disease). Orbital US found that, in all patients, the lens was normally located anatomically, and the chorioretinal complex and the subdural space of the optic nerve were of normal thickness. Retrobulbar adipose tissue (RAT) edema was found in 49 patients with active disease. Of these 49, four also exhibited eyelid edema. RAT fibrosis without muscle fibrosis was found in 21 patients, and with muscle fibrosis, in 30 patients. Although 49 patients had active AO, US-based thickness of the orbital rectus muscles was within reference intervals. In all patients, the rectus muscles were seen as hypoechogenic structures. There was a significant difference in orbital rectus muscle thickness measurements between orbital US and MRI. Thus, MRI-based thickness of medial, lateral, superior and inferior rectus muscles was significantly greater (р < 0.05) than US-based thickness of these muscles, with US demonstrating normal thickness.Conclusion: First, orbital ultrasonography found RAT edema in 49%, and RAT fibrosis in 51% of patients with GD-associated AO. Second, in all patients with active AO, orbital US provided valuable data for assessing the status of RAT and determining whether RAT edema or fibrosis was present. Third, MRI-based thickness of orbital rectus muscles was significantly (p < 0.05) greater than US-based thickness of these muscles, with US demonstrating normal thickness. Finally, because orbital US does not provide reliable data for determining orbital rectus muscle thickness, especially in active AO, it is reasonable to use orbital MRI for this purpose.
Keywords: autoimmune ophthalmopathy; Graves’ disease; ultrasound examination; magnetic resonance imaging